2006
DOI: 10.1111/j.1742-4658.2006.05304.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel N‐terminal hydrophobic motif mediates constitutive degradation of serum‐ and glucocorticoid‐induced kinase‐1 by the ubiquitin–proteasome pathway

Abstract: Serum‐ and glucocorticoid‐induced protein kinase‐1 (SGK‐1) plays a critical role in regulation of the epithelial sodium channel, ENaC. SGK‐1 also shares significant catalytic domain homology with protein kinase B (PKB/AKT‐1) and is a downstream effector of antiapoptotic phosphoinositide 3‐kinase signaling. Steady‐state levels of an active SGK‐1 are tightly regulated by rapid transcriptional activation and post‐translational modification including phosphorylation. We show here that endogenous SGK‐1 protein is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 71 publications
3
52
0
Order By: Relevance
“…Recently we have shown that the N-terminus of Sgk1 contains an amphipathic ␣-helix that targets the protein to the ER membrane (Arteaga et al, 2006;Bogusz et al, 2006). This finding posed the question of how ER localization is compatible with the functions hitherto proposed for Sgk1, some of which require translocation of Sgk1 to the nucleus.…”
Section: Sgk1 Isoforms Localize To Different Cellular Compartmentsmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently we have shown that the N-terminus of Sgk1 contains an amphipathic ␣-helix that targets the protein to the ER membrane (Arteaga et al, 2006;Bogusz et al, 2006). This finding posed the question of how ER localization is compatible with the functions hitherto proposed for Sgk1, some of which require translocation of Sgk1 to the nucleus.…”
Section: Sgk1 Isoforms Localize To Different Cellular Compartmentsmentioning
confidence: 71%
“…Posttranscriptionally, Sgk1 is activated by sequential phosphorylation on residues S422 and T253 by a still unidentified kinase (PDK2) and phosphatidylinositol-3-phosphate dependent kinase 1 (PDK1), respectively . The abundance of Sgk1 protein is maintained at low basal levels by rapid degradation mediated by the ubiquitin proteasomal machinery associated to the endoplasmic reticulum (ER) (Arteaga et al, 2006;Bogusz et al, 2006). Lastly, under certain stimuli Sgk1 translocates from the cytoplasm to the nucleus where it phosphorylates transcriptional factors .…”
Section: Introductionmentioning
confidence: 99%
“…The canonical SGK1 contains an amphipathic ␣-helix that targets the protein to the cytosolic surface of the endoplasmic reticulum (22,29); SGK3 contains a PX domain that binds to PtdIns(3)P, thereby targeting the protein to early endosomes (30); SGK1.1 uses a cluster of cationic and large hydrophobic residues to bind PtdIns(4,5)P 2 and tether the protein to the plasma membrane. Such motifs have been described and shown to be necessary for targeting small guanosine triphosphatases (GTPases) from the Ras, Rho, Arf, and Rab subfamilies to the plasma membrane (24).…”
Section: Discussionmentioning
confidence: 99%
“…Of note however and in contrast to BAX, we failed to see enhanced SGK expression at the protein level upon IKAP/hELP1 depletion (data not shown). This may be due to the intrinsic instability of SGK, which is known to be quickly degraded through the proteasome pathway [44]. In any case, we clearly show here that the upregulated SGK mRNA expression requires wild type p53 as SGK is no longer induced in p53 deficient HCT116 or in HT29 cells, where p53 is not functional.…”
Section: Discussionmentioning
confidence: 63%